Legal Aspects of Charging Fiduciary Guarantees in Money Lending and Borrowing Cases - Sitepu, Reza Athaya; Harahap, Mhd. Yadi; Lubis, Rizki Nur Fadilah; Andrivina, Annisa; Ginting, Erika Damayanti; Yulianda, Riska (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Lending and borrowing money has been a known practice in society for a long time, when money has become a commonly used means of transaction. Guarantee law is always related to economic law because growth in sectors such as industry, trade, companies, transportation, and others requires access to funds. Financial institutions, both banks and non-banks, provide funds for development, which require collateral for the return of the loaned funds. The question discussed in this research is "How is the burden of fiduciary guarantees in cases of borrowing and borrowing money?